Empathetic, persistent and female: A snapshot of oral health therapy students in Australia and New Zealand. (24th May 2021) - Stormon, Nicole; Beckett, Deanna; Gardner, Suzanne; Keshoor, Smita; Smart, Karen; Wallace, Linda; Ford, Pauline J.; Satur, Julie; Eley, Diann
Abstract: Introduction: Dental therapists, hygienists and oral health therapists constitute up to a third of the dental workforce in Australia and New Zealand. Personality is often explored in health professions to provide insights into traits that are conducive to workforce retention and to assist in planning and training. This study aimed to investigate the current demographic and personality characteristics of oral health students in Australia and New Zealand. Materials and Methods: Students in years one to three of all eight undergraduate Bachelor of Oral Health programs in Australia and New Zealand were invited to complete an online survey. The survey measured activities prior to entering into oral health, career intentions and included a personality questionnaire, the Temperament and Character Inventory (TCI). Results: Three quarters of participants ( n = 336; 30% response rate; females = 90%) were single, from an urban area and 20–29 years of age. Oral health students overall portrayed high trait levels of Persistence and Cooperativeness. Cluster analysis of TCI traits identified three groups. Groups of students with high Persistence and Cooperativeness tended to be older, were working in non‐dental and dental careers prior to their degree and were interested in working in regional areas after graduation. Conclusions: Students with high levels of persistence and cooperativeness were interested in working in regional areas after graduation, highlighting the importance of industriousness and persistence in overcoming barriers to practicing in regional areas. Further research is warranted to investigate barriers and enablers in recruitment and retention of males in a primarily female dominated profession.